Analysis of Utilization of Regional Assets Against Regional Original Income (Case Study of Road and Bridge Maintenance UPTD) - Mediaty, Mediaty; Kartini, Kartini; Ashar, Ainun Wafiyah; Patiju, Ashmad; Harlina, Harlina; Bakeng, Hasmiriyanti (Universitas Negeri Surabaya, 2024)
This study aims to analyze the utilization of Regional Property (BMD) in the Regional Technical Implementation Unit (UPTD) of Road and Bridge Maintenance to increase Regional Original Revenue (PAD). BMD utilization in the use of heavy equipment has a low contribution to West Sulawesi PAD. However, when viewed from the current phenomenon, it should have a high contribution with road improvements from 2022 to the present. As for how to utilize regional property by leasing, borrowing, cooperative utilization, building for handover, building for handover and cooperation in providing infrastructure. The research method used in this research is to use quantitative research methods. The results of this study are that currently the form of asset utilization carried out by the UPTD Maintenance of Roads and Bridges is rent, the results received from asset utilization have not made a significant contribution to increasing PAD, asset management that is less than optimal due to there are still damaged tools. However, the budget for BMD maintenance costs at the UPTD of Road and Bridge Maintenance is still low so that the use of heavy equipment has not made a significant contribution to the PAD of West Sulawesi Province.